ESTETIKA KARAWITAN TRADISI SUNDA - Heri Herdini (PANGGUNG, 2012)
The problem of "aesthetics" related not only to the "text" or the art form itself, but also to the mindset and worldview of the communities on "the world" and "the nature of human life." Behind the musical form itself, there lies the mindset of Sundanese people which formed the basis for the "text" of karawitan. The understanding on "karawitan context" is, therefore, important. It means that "text" and "context" constitute "two sides of the same coin" which are interrelated to each other. This is the subject matter to be discussed in this paper.Â Â Â Â Â Â Â Â Â Â Â  This paper is a philosophical study in order to find "the aesthetic of traditional karawitan" which has not been revealed so far. To reveal this problem the writer uses the theory of "Antagonistic Dualism" by Jakob Sumardjo. Based on the analysis to the "text" and "context" of Sundanese traditional karawitan, it is concluded that "the aesthetic of Sundanese traditional karawitan" comes from the concept of "masagi" that in substance may produce "pola tigaâ€ (pattern of three) as a reflection of the culture of tritangtu, those are: tekad, ucap, and lampah.Â Keywords: Aesthetic,traditional karawitan, pola tiga.Â